1990
DOI: 10.1002/bjs.1800770220
|View full text |Cite
|
Sign up to set email alerts
|

Common femoral artery volume flow in peripheral vascular disease

Abstract: Common femoral artery volume flow was measured at rest and during postocclusive reactive hyperaemia in 80 normal subjects and 67 patients with radiological evidence of occlusive peripheral vascular disease. At rest, means(s.d.) common femoral artery volume flow in normal subjects (344(135) ml/min) and all patients with peripheral vascular disease (401(168) ml/min) was not significantly different. During postocclusive reactive hyperaemia, mean(s.d.) peak flow was significantly higher in normal subjects (1951(43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…Our data show that popliteal artery flow in patients with stable intermittent claudication in the horizontal position is not different from that of normal subjects (P = .97). This is in accord with data by Lewis et al, 27 who reported that the supine common femoral artery vFl in limbs of patients with intermittent claudication (390 mL/ min) does not differ significantly from that of normal subjects (344 mL/min). However, as popliteal artery flow in the present study, as in most previous pertinent ones, has not been normalized for limb size, direct intergroup comparisons should be interpreted with caution.…”
Section: Commentsupporting
confidence: 93%
“…Our data show that popliteal artery flow in patients with stable intermittent claudication in the horizontal position is not different from that of normal subjects (P = .97). This is in accord with data by Lewis et al, 27 who reported that the supine common femoral artery vFl in limbs of patients with intermittent claudication (390 mL/ min) does not differ significantly from that of normal subjects (344 mL/min). However, as popliteal artery flow in the present study, as in most previous pertinent ones, has not been normalized for limb size, direct intergroup comparisons should be interpreted with caution.…”
Section: Commentsupporting
confidence: 93%
“…In the present study, the BF was 455 Ϯ 25 ml/min in RCFA and 424 Ϯ 27 ml/min in LCFA. These values are in the same range as the values (in ml/min) of 450-886 (1), 301 Ϯ 81 (ϮSD) (17), and 390 Ϯ 20 (65), as measured by using indicator dilution, and 376 Ϯ 154 (44), 226.5 Ϯ 28.6 (15), 344 (36), and 350-367 (29), as measured by Doppler ultrasound. Furthermore, Ganz et al (19) reported a value of 383-766 ml/min by using thermodilution, and Vä nttinen (62) reported a value of 239 ml/min by using electromagnetic flowmetry.…”
Section: Validation Of Bf Value At Resting Levelsupporting
confidence: 69%
“…Blood flow in the femoral arteries was 316 ± 97 ml/min in the LFA and 313 ± 83 ml/min in the RFA. These values are in the same range as those of 450-886 ml/min [32], 301 ± 81 ml/min [33], and 390 ± 20 ml/min [34] measured using indicator dilution; and 376 ± 154 ml/min [35], 226.5 ± 28.6 ml/min [31], 344 ml/min [36], and 350-367 ml/min [37] measured by Doppler ultrasound. Furthermore, Ganz et al [38] reported a value of 383-766 ml/min by thermodilution, and Vänttinen [39] reported a value of 239 ml/min using electromagnetic flowmetry.…”
Section: Consideration Of the Physiological Aspect Of The Three Artersupporting
confidence: 60%